“A book to end all books about mathematical modelling” - Jensen, Kasper Bjering Søby (MONA - Matematik- og Naturfagsdidaktik, 2020)
Boganmeldelse: Magens Niss & Werner Blum: The Learning and Teaching of Mathematical Modelling, Routledge, 2020